Media dalam Kehidupan Masyarakat - Afif Muhtar, Alvin; Rohman, Miftakhul (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The media plays a crucial role in daily life, serving as a communicator, catalyst for change, and a platform for interaction. Its significance in society cannot be understated, holding a pivotal position that extends to both urban and rural communities. With the proliferation of various media outlets, including the pervasive influence of social media, communication has experienced a significant expansion. The presence of media has become inseparable from people's lives, shaping, and reflecting societal dynamics